Peningkatan Literasi melalui Modul dan Sticker Interaktif Terkait Mitigasi Bencana Alam - Abdul Kadir Jaelani; Randy Ferdiansyah Hasibuan; Muhammad Tesar Trisetya; Fani Allyssa Dwita Putri; Risma Aulia Puteri; Fatkhia Akhsani; Dina Tya Kumala; Desvita Nurul Ilmi; Athaya Qonitah Hadi; Farah Ika Melati; Elysa Dwi Apriliana (Universitas Muhammadiyah Manado, 2026)
Indonesia is a country with a high level of vulnerability to various natural disasters, making it essential to improve disaster mitigation literacy from an early age, particularly among primary school pupils. However, disaster mitigation education in schools is often still theoretical and lacks engaging and contextually relevant learning materials. Therefore, this initiative aims to enhance pupils’ understanding of disaster mitigation and environmental awareness through the use of an interactive magazine module accompanied by educational stickers. This community service activity was carried out at Giriwungu Primary School, Girirejo Village, Imogiri Sub-district, Bantul Regency, targeting Year 3 primary school pupils. The implementation method employed an educational-participatory approach through several stages of activity, namely the screening of educational videos, the distribution of interactive magazine modules, independent reading activities, the presentation of picture stories, and interactive quizzes to assess pupils’ understanding. The results of the activity showed that the pupils demonstrated high levels of enthusiasm and participation throughout the session, and the majority were able to grasp the basic concepts of waste management and the importance of protecting the environment as part of disaster mitigation efforts. Consequently, the use of interactive magazine modules can serve as an effective literacy tool for enhancing pupils’ understanding and fostering awareness of environmental care and disaster mitigation from an early age.